Analisis Reaksi Investor Sebelum Pengumuman dan Setelah Pencabutan Suspensi Saham - Hamdani Arifulsyah Rangkuti; Fifitri Ali; Abdi Bhayangkara (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2021)
AbstractThe purpose of this research is to analyze descriptively qualitatively to test whether the abnormal return, trading Volume activity and Bid-Aks spread have a positive or negative value before the announcement suspension and after unsuspension. After that, testing with a different test (paired sample t-test). This research is an event study, using an estimated period of 5 days before the announcement of the suspension, and 5 days after the withdrawal of the suspension (unsuspension), within the period of observation in the year 2019. The sample in this study was 75 companies that announced the stock suspension. as well as announcing stock unsuspension in 2019. The results of this study show that the average abnormal return, trading Volume activity and Bid-Aks spread show a positive value both before the announcement of the stock suspension and after the stock unsuspension. Meanwhile, for the different test results (paired sample t-test), there is a significant difference before the announcement of stock suspension and after stock unsuspension for the abnormal return variable and the Bid-Aks spread, while the trading Volume activity must be excluded from the study because SPSS did not include it so the exclude variable category.  Abstrak Riset ini bertujuan menganalisis secara deskriptif kualitatif apakah abnormal return, Trading Volume activity dan Bid-Aks spread memiliki nilai positif atau negatif pada saat sebelum pengumunan dan setelah pencabutan suspensi saham. Pengujian berikutnya adalah dengan melakukan uji beda berpasangan (paired sample t-test). Periode penelitian ini adalah 5 hari sebelum pengumuman suspensi saham, dan 5 hari setelah penarikan suspensi saham (unsuspensi), dalam rentang waktu pengamatan dari selama tahun 2019. Sebanyak 75 perusahaan yang mengumumkan suspensi dan unsuspensi saham selama tahun 2019. Hasil penelitian ini menunjukkan bahwa rata-rata Abnormal Return, Trading Volume Activity dan Bid-Aks Spread menunjukkan nilai yang positif baik sebelum pengumuman suspensi saham, maupun setelah unsuspensi saham. Sementara untuk hasil uji bedanya, beda yang cukup nyata sebelum pengumuman suspensi saham dan setelah unsuspensi saham untuk variabel Abnormal Return  dan Bid-Aks Spread, sementara untuk variabel Trading Volume Activity dikeluarkan dari penelitian karena di SPSS termasuk kedalam kategori exclude variable.